2019
DOI: 10.1002/pssr.201900201
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hydrogen‐Rich Silicon Nitride Material Properties on Light‐Induced Lifetime Degradation in Multicrystalline Silicon

Abstract: The root cause of “Light and Elevated Temperature Induced Degradation” (LeTID) of the carrier lifetime in multicrystalline silicon (mc‐Si) wafers is investigated by depositing hydrogen‐rich silicon nitride (SiNx:H) films of different compositions on boron‐doped mc‐Si wafers. The extent of LeTID observed in mc‐Si after rapid thermal annealing (RTA) shows a positive correlation with the amount of hydrogen introduced from the SiNx:H layers into the bulk. The concentration of in‐diffused hydrogen is quantified via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 14 publications
0
40
0
Order By: Relevance
“…Note that various works have observed a strong correlation between the SiN x film properties, the firing conditions (temperature and cooling rate), and the stability of mc‐Si wafers and solar cells upon illumination at elevated temperature . It was suggested that the so‐called light and elevated temperature‐induced degradation (LeTID) mechanism in mc‐Si materials is related to hydrogen in diffusion from SiN x and is triggered by the rapid cooling after the firing process .…”
Section: Resultsmentioning
confidence: 99%
“…Note that various works have observed a strong correlation between the SiN x film properties, the firing conditions (temperature and cooling rate), and the stability of mc‐Si wafers and solar cells upon illumination at elevated temperature . It was suggested that the so‐called light and elevated temperature‐induced degradation (LeTID) mechanism in mc‐Si materials is related to hydrogen in diffusion from SiN x and is triggered by the rapid cooling after the firing process .…”
Section: Resultsmentioning
confidence: 99%
“…The maximum of ∆N leq is also influenced by the H out-diffusion rates of both SiN x :H layers. Thus, as pointed out in a recent publication [28], bulk H density measurements are necessary to confirm the impact of SiN x :H layer properties on LeTID kinetics, which are beyond the scope of this article.…”
Section: Different Sin X :H Layer Deposition Toolsmentioning
confidence: 96%
“…The maximum amount of hydrogen is hence introduced into the silicon bulk for the silicon‐rich SiN x layers with a refractive index of n = 2.3, in agreement with the recent findings of another study. [ 22 ] In addition, Figure 2a demonstrates that [H tot ] critically depends on the peak temperature: At low peak temperatures, [H tot ] increases with increasing ϑ peak , whereas at high peak temperatures, [H tot ] decreases with increasing ϑ peak . The maximum of [H tot ] as a function of ϑ peak depends on the silicon content of the SiN x layer.…”
Section: Figurementioning
confidence: 99%